Improved HFACS on Human Factors of Construction Accidents: A China Perspective. (18th July 2018) - Ye, Gui; Tan, Qin; Gong, Xiaoli; Xiang, Qingting; Wang, Yuhe; Liu, Qinjun
Abstract : Human errors are one of the major contributors of accidents. In order to improve the safety performance, human errors have to be addressed. Human Factors Analysis and Classification System (HFACS) has been developed as an analytical framework for the investigation of the role of human errors in aviation accidents. However, the HFACS framework did not reveal the relationships describing the effect among diverse factors at different levels. Similarly, its interior structure was not exposed. As a result, it is difficult to identify critical paths and key factors. Therefore, an improved Human Factors Analysis and Classification System in the construction industry (I-HFACS) was developed in this study. An analytical I-HFACS mechanism was designed to interpret how activities and decisions made by upper management lead to operator errors and subsequent accidents. Critical paths were highlighted. Similarly, key human factors were identified, that is, "regulatory factors, " "organizational process, " "supervisory violations, " "adverse spiritual state, " "skill underutilization, " "skill-based errors, " and "violations." Findings provided useful references for the construction industry to improve the safety performance.